An expert survey on chamber measurement techniques and approaches for calculation and quality control of methane fluxes - Katharina Jentzsch; Lona van Delden; Matthias Fuchs; Kathleen R Hall; Claire C Treat (PANGAEA, 2025)
This data set contains the responses to an expert survey on chamber measurements of methane (CH4) fluxes from 36 participants working in 11 countries each of whom had at least one field season of experience in chamber measurements. The expert survey covered questions on demographic information, the research sites and research topics of the participants, their measurement setups, and their flux calculation methods. The survey, furthermore, contained an exercise on visual quality control in which the participants were asked to decide between keeping or discarding 12 chamber measurements or parts of them based on the behavior of the CH4, carbon dioxide (CO2), and water vapor (H2O) concentrations measured in the chamber over time and to explain their decisions. We calculated the CH4 fluxes based on a linear fit to the time periods chosen by the participants. The calculated CH4 fluxes as well as the raw chamber measurement data for this visual quality control are included in this data set. The survey results allow us to assess the similarities and the differences between the approaches to measure, process, and evaluate chamber CH4 fluxes used by the different flux experts. This knowledge can help at harmonizing chamber measurement methods for CH4 fluxes and thus at identifying and eliminating sources of uncertainty for data synthesis products which combine data sets processed by various researchers. A reassessment of chamber techniques becomes particularly important in the light of an increasing use of new multigas analyzers whose high-frequency and high-accuracy CH4 concentration measurements both open new possibilities and pose new challenges in the interpretation of chamber measurements.